Boosting photovoltaic performance of dye-sensitized solar cells using silver nanoparticle-decorated N,S-co-doped-TiO2 photoanode - Lim, Su Pei; Pandikumar, Alagarsamy; Lim, Hong Ngee; Ramaraj, Ramasamy; Huang, Nay Ming (Nature Publishing Group, 2015)
A silver nanoparticle-decorated N,S-co-doped TiO2 nanocomposite was successfully prepared and used as an efficient photoanode in high-performance dye-sensitized solar cells (DSSCs) with N719 dye. The DSSCs assembled with the N,S-TiO2@Ag-modified photoanode demonstrated an enhanced solar-to-electrical energy conversion efficiency of 8.22%, which was better than that of a DSSC photoanode composed of unmodified TiO2 (2.57%) under full sunlight illumination (100mWcm−2 , AM 1.5 G). This enhanced efficiency was mainly attributed to the reduced band gap energy, improved interfacial charge transfer, and retarded charge recombination process. The influence of the Ag content on the overall efficiency was also investigated, and the optimum Ag content with N,S-TiO2 was found to be 20wt%. Because of the enhanced solar energy conversion efficiency of the N,STiO2@Ag nanocomposite, it should be considered as a potential photoanode for high-performance DSSCs.